Peran Orangtua dalam Upaya Menumbuhkan Rasa Percaya Diri Anak Usia Dini - Vivilia Vivone Vriska Macarau; Kalis Stevanus (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2022)
Self-confidence is very influential on a person’s behavior. Not all children have high confidence. Even children at an early age can experience feelings of inferiority, lack of enthusiasm, and pessimism when faced with problems. Low self-esteem can usually appear in various negative emotions, such as discomfort, inability, fear of failure, and soon. Trust is an urgent need for every individual, including in early childhood. This article aims to explain the importance of children's self-confidence and how parents try to increase children's self-confidence early, so that they do not judge themselves too low, instead have a positive attitude toward themselves and respect themselves and their abilities. This article uses a literature approach, with techniques of collecting data from relevant literature and analyzing them descriptively, logically, and systematically. This article emphasizes that the role of parents in increasing children's self-confidence from an early age is to love children with unconditional love; use good words to build; instill responsibility; provide opportunities for children to choose and make decisions; dare to say